Commitment-based analysis of organizations : dealing with inconsistencies - Nawaz, Shameem Shah. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2007., 2007)
Multiagent organizations are composed of interacting agents. These agents are usually assigned with roles and have clearly defined tasks so that organizational goals are effectively materialized. Formal specifications of multiagent organizations allow organization designers to analyze existing organizations and reason about possible changes in the organizations. Systematic analysis of organizations can help identify potential errors in the organization early on. In this thesis, we study a commitment-based approach for specifying organizations and then detecting and resolving inconsistencies and conflicts in the specifications. Additionally, we have developed a software tool to help organization designers with creation and manipulation of organizational specifications. The tool can check the workings of an organization for inconsistencies and signal the possibility or the certainty of a conflict during execution and can provide a set of suggestions for resolving conflicts. Furthermore, the tool can semi-automate the task of combining two organizational work-flows, by aggregating related properties of the organizations; and can present a higher level view of organizations. We illustrate these properties using a case study that deals with two organizations.
Keywords: Intelligent agents (Computer software)